IMPLEMENTASI ETIKA BISNIS DALAM PELAYANAN BIRO UMROH DAN HAJI: STUDI KASUS PADA PT.SAFARI GLOBAL PERKASA - Syamsul Aman; Amrina Yulfajar (Ekomania, 2023)
This article explains that ethical values are important values that are included as the spirit of business activities. This can be a distinct advantage for the company, and in the end it will be more attractive to grow consumer loyalty. This research is a research that is supported by qualitative and descriptive qualitative methods which aims to explain and describe how business ethics can provide the best service in carrying out the Hajj and Umrah pilgrimages as a very good way of working which is carried out by PT Safari global perkasa. In this study shows the values of business ethics applied by PT. Mighty Global Safari, The first is the values of honesty in every service provided to consumers. Second, humility serves the value of consumers in the form of appreciation and wisdom. Third, the value of keeping promises in serving Hajj and Umrah from what is explained and what has been written to consumers. Finally, the value of responsibility in each implementation in serving consumers.